What is fundamental for the maintenance of excellence in scientific periodicals? - Parrish II, Richard K. (Revista de Medicina, 2016)
I am honored to contribute to this centenary edition of what will mark a landmark in the publication of medical science for the Revista de Medicina from the University of Sao Paulo Medical School. In response to the question, “What is fundamental for the maintenance of excellence in scientific periodicals?”, as an author, clinician scientist, and the Editor in Chief of the American Journal of Ophthalmology, my answer has remained the same. The criteria for meaningful scientific contributions in clinical medicine are threefold. [...]